Real estate price bubble in the Republic of Croatia - Mustać, Josipa (Oeconomica Jadertina, 2019)
The market balloons are fast-growing price phenomena, followed by their dramatic drop. In some parts of Croatia - the coastline and in the city of Zagreb, real estate prices have been growing drastically, considering the period from the year 2000. The global economic crisis occurred in the United States came 2008 due to the inflation of real estate prices, which also transferred to the Croatian economy due to the flooding effect from one market to another. This paper examines whether the same case is happening in Croatia today, namely whether the real estate price increase in Croatia was justified or they are balloons that will suddenly break. Real estate prices in Croatia are growing due to several factors, such as increased real estate demand for tourist rental, housing loans subsidies for young people and increased real estate demand by foreigners. If there is a significant drop in tourist activity in Croatia, real estate prices could fall dramatically.